Implementation of Smart Indonesia Card Policy for College at Private Universities in Palu City - Sussanti Sussanti; M Syukur; Syugiarto Syugiarto (Khazanah Sosial, 2026)
This study focuses on the implementation of the Indonesia Smart Card for College (KIP Kuliah) Program in private universities (PTS) in Palu City, with the main objective of identifying factors that influence the effectiveness of the policy based on the George C. Edwards III Policy Implementation Model. The study was conducted using a qualitative approach through Literature Review and Field research. The primary data collection process involved interviews with LLDIKTI Region XVI and KIP administrators at Palu PTS. The research results found that the KIP Kuliah program has had a real impact in increasing access to higher education for economically disadvantaged groups, but still faces a number of key issues: less than optimal policy communication to recipients, limited infrastructure and human resource capacity of administrators, variations in the disposition of implementers, and an inefficient and uncoordinated administrative bureaucracy. Problems with recipient data validation and program socialization also pose significant obstacles that impact the accuracy of scholarship distribution. Recommendations for strengthening are directed at improving the quality of communication and HR training, simplifying bureaucratic procedures, and integrating a continuous monitoring and evaluation system to support the successful implementation of the program. By strengthening the four main variables of the Edwards III model, it is hoped that the KIP Kuliah program at Palu PTS will become more effective in expanding access to higher education.